Diagnostic concordance of GeneXpert HCV VL fingerstick and GeneXpert HCV viral load with RT-PCR in POCT settings among hemodialysis patients - Andri Sanityoso Sulaiman; Pringgodigdo Nugroho; Darlene Raudhatul Bahri; Desti Rachmani (PLoS ONE, 2026)
Background Hepatitis C virus (HCV) remains a significant global health concern, particularly among high-risk populations such as patients undergoing hemodialysis. Although nucleic acid testing (NAT) using RT-PCR remains the gold standard for HCV RNA detection, its centralized laboratory workflow limits accessibility. Point-of-care molecular testing (PoCT), such as the GeneXpert Fingerstick assay, offers a decentralized alternative for HCV RNA quantification. However, its analytical concordance with reference methods in Indonesian settings remains limited. Methods This study was a cross-sectional analytical concordance study involving 57 patients with chronic kidney disease (CKD) undergoing hemodialysis at Cipto Mangunkusumo and Pelni Hospitals in Jakarta. Each participant underwent HCV RNA testing using three methods: GeneXpert HCV VL Fingerstick, GeneXpert HCV VL Plasma, and Cobas TaqMan RT-PCR (as the reference standard). Agreement among methods was assessed using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and Cohen’s κ coefficient. Correlation for quantifiable values was evaluated using linear regression analysis. Results Both GeneXpert methods showed perfect concordance with the Cobas TaqMan RT-PCR, with sensitivity, specificity, PPV, and NPV all at 100%. Agreement analysis yielded a Cohen’s κ of 1.000 ( p < 0.001) for both comparisons. Quantitative correlation between methods was also strong ( R² > 0.95). Conclusion The GeneXpert HCV VL Fingerstick assay demonstrates excellent analytical agreement with conventional molecular testing and may serve as a simple, practical, decentralized alternative for monitoring HCV RNA in hemodialysis patients.